2020
DOI: 10.20944/preprints202012.0009.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Review of Fresnel Incoherent Correlation Holography with Linear and Non-Linear Correlations

Abstract: Fresnel incoherent correlation holography (FINCH) is a well-established incoherent imaging technique. In FINCH, three self-interference holograms are recorded with calculated phase differences between the two interfering, differently modulated object waves and projected into a complex hologram. The object is reconstructed without the twin image and bias terms by a numerical Fresnel back propagation of the complex hologram. A modified approach to implement FINCH by a single camera shot by pre-calibrating the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Furthermore, the beam characteristics of the two interfering beams were not manifested in the imaging characteristics in this correlation approach. A recent simulative study revealed that the performance of FINCH in the pattern recognition approach was nearly independent of the characteristics of the interfering beams [36]. Therefore, the methods developed by Bouchal and Bouchal using vortex filter could not applied for edge enhancement [38] in this case.…”
Section: Future Challengesmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, the beam characteristics of the two interfering beams were not manifested in the imaging characteristics in this correlation approach. A recent simulative study revealed that the performance of FINCH in the pattern recognition approach was nearly independent of the characteristics of the interfering beams [36]. Therefore, the methods developed by Bouchal and Bouchal using vortex filter could not applied for edge enhancement [38] in this case.…”
Section: Future Challengesmentioning
confidence: 94%
“…FINCH was proposed as a correlation between the object and Fresnel zone plates (FZP). It is based on a single on-axis interferometer and does not require any movement or multiplexing image of the scene [36,39]. So, the FINCH system is widely applied in microscope and imaging methods with a synthetic aperture.…”
Section: Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresnel incoherent correlation holography (FINCH), published in 2007 [23], was a return to the principle of self-interference and was proposed as an alternative to the scanning-based holography methods mentioned above. Following the first FINCH, many other incoherent digital holograms were proposed, with most of them based on the self-interference principle [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Fourier incoherent single-channel holography (FISCH) [39] is a typical example of using the self-interference principle, but the obtained hologram, in this case, is a 2D cosine Fourier transform of the object.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, a two-step phase-shift FINCH was developed utilizing the mathematical model of self-interference holography and implemented FINCH with two camera shots [7]. A radically different approach of single shot FINCH was demonstrated by prerecording the point spread hologram (PSH) and correlating it with the FINCH hologram of an object using non-linear reconstruction [8][9][10]. In that approach, the optical modulator of FINCH was designed based on the configuration of the first version of FINCH by randomly multiplexing two quadratic phase functions and manufactured as a passive optical element using electron beam lithography.…”
Section: Introductionmentioning
confidence: 99%